School martial bands as spaces of social inclusion for brazilian youth (Research, Society and Development, 2021)
This article revisits the dissertation entitled Memories on the agenda: a narrative about the martial band of the Escola Técnica Federal de Pelotas (ETFPEL) in the 60s and 70s (Recordações em pauta: uma narrativa sobre a banda martial da Escola Técnica Federal de Pelotas (ETFPEL) in the 60s and 70s), comparing the works discussed in its State of Knowledge and the interviews given by former members of the referred band, which integrate the dissertation as an appendix. If, at first, while the research was being carried out, the State of Knowledge was useful for the researcher to enter into the theme of school martial bands in order to build a theoretical and methodological reference for his research, here a synthesis is produced from it in the form of categories, which can be taken as representative of research on school martial bands; these categories are compared, later, with the former students interviews which are former members of the ETFPEL Band, aiming to produce interpretations and approximations between the themes, in order to understand some of the experiences that the bands aroused in their members. The result of the analysis reveals that, regardless of regionalization and the differences intrinsic to each school community, the former bands’ students recognize the experience of taking part in them as promoting spaces of inclusion and learning, both musically and as citizens.